2015
DOI: 10.3390/md13085384
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-Nephrolithe Activities and in Vitro Digestibility Studies of Three Different Cyanobacterial Pigment Extracts

Abstract: Phycobiliprotein-containing water and carotenoid-containing methanolic extracts of three different cyanobacteria, Pseudanabaena sp., Spirulina sp. and Lyngbya sp., were studied for their DPPH scavenging, iso-bolographic studies, and anti-nephrolithe activities. The best EC50 values for DPPH scavenging were in Lyngbya water (LW, 18.78 ± 1.57 mg·mg−1 DPPH) and Lyngbya methanol (LM, 59.56 ± 37.38 mg·mg−1 DPPH) extracts. Iso-bolographic analysis revealed most of the combinations of extracts were antagonistic to ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…It is soluble in water and can be easily extracted from S. platensis (Chaiklahan, Chirasuwan, & Bunnag, 2012), usually by the freezing/thawing method (forms ice crystals that cause cell disruption, facilitating the pigments' release), employing different solvents (Abalde, 1998;Kumar, Dhar, Pabbi, Kumar, & Walia, 2014;Soni, Kalavadia, Trivedi, & Madamwar, 2006). In this work, water was the solvent that allowed to extract the highest amount of phycocyanin (1.44 mg/mL, Table 1), which was significantly higher than the concentrations obtained with acetate buffer, phosphate buffer, and ethanol (Table A1, supplementary material), and also higher than the concentrations obtained in similar studies (Paliwal, Bhayani, Maurya, & Mishra, 2015). In either case, there is the possibility of losing phycocyanin during the drying and heating processes (İlter et al, 2018).…”
Section: Nutritional and Chemical Composition Of Spirulina Platensismentioning
confidence: 65%
See 1 more Smart Citation
“…It is soluble in water and can be easily extracted from S. platensis (Chaiklahan, Chirasuwan, & Bunnag, 2012), usually by the freezing/thawing method (forms ice crystals that cause cell disruption, facilitating the pigments' release), employing different solvents (Abalde, 1998;Kumar, Dhar, Pabbi, Kumar, & Walia, 2014;Soni, Kalavadia, Trivedi, & Madamwar, 2006). In this work, water was the solvent that allowed to extract the highest amount of phycocyanin (1.44 mg/mL, Table 1), which was significantly higher than the concentrations obtained with acetate buffer, phosphate buffer, and ethanol (Table A1, supplementary material), and also higher than the concentrations obtained in similar studies (Paliwal, Bhayani, Maurya, & Mishra, 2015). In either case, there is the possibility of losing phycocyanin during the drying and heating processes (İlter et al, 2018).…”
Section: Nutritional and Chemical Composition Of Spirulina Platensismentioning
confidence: 65%
“…Although other forms of tocopherols (β-and δ-tocopherol) are found in Spirulina, the antioxidant activity is mostly related with the presence of α-tocopherol, whereas βand δ-tocopherols are mainly associated with the anti-inflammatory effects (Azzi, 2018). Paliwal et al (2015), who accessed the antioxidant activity of aqueous and methanolic extracts of Spirulina sp. by the DPPH method, highlight the high content of phycocyanin in these extracts.…”
Section: Bioactive Properties Of Free and Microencapsulated Spirulinamentioning
confidence: 99%
“…Researchers have shown that antioxidants can impair enzyme activity during the digestion [ 42 ]. The interaction between phenolic compounds and digestive enzymes [ 43 ] could affect the non-covalent starch-phenolic interactions thus impeding starch degradation [ 44 , 45 ]. Additionally, the rate of sugar release may also be decreased due to the non-starchy network of fibre and protein in the system which entraps starch granules and acts as a physical barrier thus limiting enzyme accessibility [ 28 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…and Lyngbya sp. were also suggested as antiurolithiasis (prevention against kidney stone disease) in in vitro assays by Paliwal et al [ 25 ]. Paliwal et al [ 25 ] also evaluated antioxidant capacity, in which Lyngbya sp.…”
Section: Applications Of Carotenoids From Cyanobacteriamentioning
confidence: 99%
“…were also suggested as antiurolithiasis (prevention against kidney stone disease) in in vitro assays by Paliwal et al [ 25 ]. Paliwal et al [ 25 ] also evaluated antioxidant capacity, in which Lyngbya sp. methanolic extract containing myxoxanthophyll, zeaxanthin, canthaxanthin, and α- and β-carotenes, was the one with the highest IC 50 for DPPH • scavenging assay (59.56 mg.mg DPPH −1 ).…”
Section: Applications Of Carotenoids From Cyanobacteriamentioning
confidence: 99%